Bridging the Gap: Genetic Counseling, Islamic Bioethics, Challenges, and Recommendations - Javaid, Iqra; Mannan, Abdul; Khan, Mariam; Fatima, Aliza; Danish, Muhammad (Indus Journal of Bioscience Research, 2025)
This paper examines the intersection between genetic counseling, testing, and Islamic bioethics, with a particular emphasis on the challenges faced by Muslim communities and the often neglected experiences of migrants and refugees. In predominantly Muslim nations, the high prevalence of consanguineous marriages significantly contributes to the burden of genetic disorders such as sickle cell anaemia and β-thalassemia. While advancements in genetic testing and prenatal diagnostics have improved early detection, there remain significant gaps in ethical guidance, accessibility, and training. Muslim communities face additional challenges, including language barriers, cultural displacement, and inconsistent healthcare. This study investigates these gaps, explores emerging ethical issues associated with technologies such as CRISPR, and proposes frameworks for culturally sensitive genetic counseling.